2023
DOI: 10.1038/s41598-023-34142-7
|View full text |Cite
|
Sign up to set email alerts
|

Type III Gustilo–Anderson open fracture does not justify routine prophylactic Gram-negative antibiotic coverage

Abstract: Postoperative surgical site infection (SSI) is common in open long bone fractures, so early administration of prophylactic antibiotics is critical to prevent SSI. However, the necessity of initial broad-spectrum coverage for Gram-positive and -negative pathogens remains unclear. The purpose of this study was to clarify the effectiveness of prophylactic broad-spectrum antibiotics in a large, national-wide sample. We reviewed an open fracture database of prospectively collected data from 111 institutions managed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Surgical site infections, the most common health care-acquired infections, are associated with the emergence of postoperative infected with multidrug-resistant bacteria [ 7 , 28 32 ]. Previous studies reported that the postoperative wound infection rate of GA classification type III can be even as high as 50% or more [ 8 , 11 , 33 ], which is itself associated with higher postoperative wound infection of fractures [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surgical site infections, the most common health care-acquired infections, are associated with the emergence of postoperative infected with multidrug-resistant bacteria [ 7 , 28 32 ]. Previous studies reported that the postoperative wound infection rate of GA classification type III can be even as high as 50% or more [ 8 , 11 , 33 ], which is itself associated with higher postoperative wound infection of fractures [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports on etiological characteristics after regrafting of severe traumatic mutilation of major limbs were limited. For patients with type III open fractures, gram-negative bacilli should be covered in addition to gram-positive bacilli, for which the evidence of evidence-based medicine was insufficient [ 7 , 13 , 14 , 22 ]. We here found the main pathogen distribution characteristics, which may provide targeted basis for the use of prophylactic antibiotics in patients in these regional centers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment process was divided into three steps. In the first stage, at the emergency department, intravenous second-generation cephalosporin antibiotics 9 , 10 (cefuroxime) were administered as soon as possible after the patient entered the hospital. Initial debridement of the devitalised and contaminated tissues was performed by a senior doctor using loupe magnification, tourniquet control, and irrigation with 9 L of solution.…”
Section: Surgical Techniquementioning
confidence: 99%